Brucellosis in Colombia: Current Status and Challenges in the Control of an Endemic Disease - Avila-Granados, Lisa M.; Garcia-Gonzalez, Daniel G.; Zambrano-Varon, Jorge L.; Arenas-Gamboa, Angela M. (Frontiers in Veterinary Science, 2019)
Brucellosis is a zoonosis of nearly worldwide distribution. The disease is considered to be endemic in most of the developing countries with a substantial impact on both human and animal health as well as on the economy. The aim of this scoping review is to provide an overview of the brucellosis status in Colombia and the factors associated with its persistence, to highlight the strengths and gaps of the adopted countermeasures and to supply evidence to policy-makers on the best approaches to mitigate the disease burden. Due to the presence of brucellosis in several susceptible production livestock systems scattered throughout the country, a plan for its control, prevention and eradication was established almost 20 years ago. However, despite extensive efforts, brucellosis prevalence has fluctuated over the years without any trend of decreasing. The restricted budget allocated for brucellosis control is a limiting factor for the success of the program. For instance, the absence of indemnities for farmers results in infected animals remaining on farms which potentially increases the risk of disease spread. Likewise, disease surveillance is restricted to Brucella abortus and excludes other Brucella species of importance such as B. melitensis and B. suis. The countermeasures are mostly focused on cattle and only a few actions are in place for the management of brucellosis in other livestock species. In humans, cases of brucellosis are annually diagnosed, although the disease remains highly underreported. High impact educational and training programs are required to address the disease in a comprehensive manner, including vulnerable groups such as traditional smallholders and low-productivity regions, as well as other stakeholders such as healthcare and veterinary authorities. Important financial investments based on sustained cooperation between governmental institutions, industry, and farmers are important for developing affordable and effective strategies to control the disease.